Information needs of young people with cerebral palsy and their families during the transition to adulthood: a scoping review - Freeman Matthew; Stewart Debra; Cunningham Charles E.; Gorter Jan Willem (De Gruyter, 2018)
The transition to adulthood is a developmental phase which occurs as young people move from adolescence into adulthood. Young people with disabilities, including cerebral palsy (CP), and their families have reported challenges during the transition to adulthood because they are required to move to adult supports and services, which are often fragmented and bring about new questions and expectations to find necessary supports. Young people and their parents have been found to lack information about where to find services in adulthood, how to access the services and what to ask during the transitional process. The aim of this scoping review was to explore the information needs of young people with CP and their families during the transition to adulthood. The goal is to map the current published evidence within the transition to adulthood literature base to explore what is known about information needs during the transition to adulthood of young people with CP and their parents. This review seeks to synthesize what is known about information content, timing, methods of provision and delivery. Databases searched were OVID Medline, CINAL, ERIC, EMBASE, PsycINFO, Web of Science, Social Science Abstracts and Sociological Abstracts. Initially 675 articles were retrieved. Four hundred and forty-two articles were selected for title review. Two hundred and five articles remained for abstract review. Seventeen articles were included for full-text review. Eleven articles were included in this review. Data were organized into five themes: (1) identified information needs during the transition to adulthood (content), (2) identified recommended providers of information during the transition to adulthood (who), (3) identified delivery methods of information during the transition to adulthood (how), (4) identified timing of information delivery of information during the transition to adulthood (when) and (5) location of information provided during the transition to adulthood (where). This review found that young people with CP, their families and adult providers all possess information needs during the transition to adulthood. Young people with CP and their families seek information about what adult services will look like and how to access supports. Adult providers require information about CP. Youth with CP prefer individualized information be delivered to them when needed rather than presented in group sessions or via paper handout. Other recommendations included the development of parent support networks to assist parents in the transition to adulthood. The opportunity to learn from real-life experiences was also viewed as an important source of information as well as method to provide information.